Dysmenorrhea, Endometriosis and Chronic Pelvic Pain in Adolescents - Aalia Sachedin; Nicole Todd (Galenos Yayincilik, 2020)
Most adolescents will experience discomfort during menstruation. Due to normalization of dysmenorrhea, there is delay to diagnosis and treatment. Non-steroidal anti-inflammatories are a first line treatment. Adolescents can safely be offered menstrual suppression with combined hormonal contraception, and progestin-only options. When the above are ineffective, gonadotropin releasing hormone agonists with add back treatment can be considered. Transabdominal ultrasound is indicated when first line treatments do not improve symptoms. Endometriosis should be considered in adolescents who experience ongoing pain despite medical treatment. If laparoscopy is performed and endometriosis visualized, it should be treated with either excision or ablation. Women with endometriosis should be counselled on menstrual suppression until fertility is desired. Management of chronic pain requires the involvement of a multi-disciplinary team.